Psychopathology and the ability to do otherwise - Pickard, H (Wiley, 2015)
When philosophers want an example of a person who lacks the ability to do otherwise, they turn to psychopathology. Addicts, agoraphobics, kleptomaniacs, neurotics, obsessives, and even psychopathic serial murderers, are all purportedly subject to irresistible desires that compel the person to act: no alternative possibility is supposed to exist. I argue that this conception of psychopathology is false and offer an empirically and clinically informed understanding of disorders of agency which preserves the ability to do otherwise. First, I appeal to standard clinical treatment for disorders of agency and argue that it undermines this conception of psychopathology. Second, I offer a detailed discussion of addiction, where our knowledge of the neurobiological mechanisms underpinning the disorder is relatively advanced. I argue that neurobiology notwithstanding, addiction is not a form of compulsion and I explain how addiction can impair behavioural control without extinguishing it. Third, I step back from addiction, and briefly sketch what the philosophical landscape more generally looks like without psychopathological compulsion: we lose our standard purported real-world example of psychologically determined action. I conclude by reflecting on the centrality of choice and free will to our concept of action, and their potency within clinical treatment for disorders of agency. © 2013 Philosophy and Phenomenological Research, LLC.